PERAN ORANG TUA DALAM MENINGKATKAN PRESTASI BELAJAR IPAS KELAS IV SD NEGERI 040448 KABANJAHE - Anggreini Flower Br Sembiring; Johannes Keliat; Yosefo Gule (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the role of parents in improving the science achievement of fourth-grade students at State Elementary School 040448 Kabanjahe and to identify the obstacles parents face in supporting their children's learning process. This study used a qualitative approach with a descriptive research method. The population in this study was all 32 fourth-grade students at State Elementary School 040448 Kabanjahe. Data collection techniques used a questionnaire to measure parental role and documentation to obtain data on students' science achievement. Before use, the research instrument was tested for validity and reliability. The results of the validity test indicated that 22 items were valid and suitable for use as a data collection tool. Data analysis was conducted using descriptive and inferential statistics, namely the Pearson correlation test and simple linear regression. The results of the study indicate that parental involvement is in the very good category, with an average percentage of 87.17%. Students' social studies learning achievement is also in the good category, with an average score of 90.38. The correlation test results indicate a positive and significant relationship between parental involvement and students' social studies learning achievement, with a correlation coefficient of 0.830 and a significance level of 0.000 <0.05. The regression test results indicate that parental involvement significantly influences students' social studies learning achievement. Based on these results, it can be concluded that the better the role of parents in providing guidance, motivation, supervision, and learning facilities, the higher the students' social studies learning achievement. Therefore, parental involvement in their children's education is crucial for improving student learning success.